2021
DOI: 10.1016/j.asmr.2021.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Wide Variability of Pediatric Knee Arthroscopy Case Volume in Orthopaedic Surgery Residency

Abstract: The purpose of this study was to evaluate orthpaedic surgery resident case volume and variability for adult and pediatric knee arthroscopy from 2016 to 2020. Methods: The Accreditation Council for Graduate Medical Education surgical case log data from 2016 to 2020 for graduating United States orthpaedic surgery residents were analyzed. The average number of total (adult and pediatric), adult, and pediatric knee arthroscopy cases were compared from 2016 to 2020. The 10th and 90th percentiles of case volumes for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
(37 reference statements)
0
4
0
Order By: Relevance
“… 3 , 4 , 5 , 6 , 7 Despite this increase, knee arthroscopy case volume often depends on the residency and available cases. 1 , 2 In addition, subjective reporting by residents revealed that a majority lacked confidence in performing arthroscopies compared with open procedures. 13…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 4 , 5 , 6 , 7 Despite this increase, knee arthroscopy case volume often depends on the residency and available cases. 1 , 2 In addition, subjective reporting by residents revealed that a majority lacked confidence in performing arthroscopies compared with open procedures. 13…”
Section: Discussionmentioning
confidence: 99%
“…There is a vast difference in reported case volume of pediatric knee arthroscopies compared with adult knee arthroscopies among resident physicians. 1 , 2 This disparity raises concern, especially as we see more children participating in sports, resulting in a concomitant increase in both pediatric knee injuries and subsequent arthroscopies. 3 , 4 , 5 , 6 , 7 Although the fundamentals of knee arthroscopy in the adult population are well documented, there is a paucity of literature surrounding basic pediatric knee arthroscopy, leading to potential complications and poor outcomes.…”
mentioning
confidence: 99%
“…According to a recent nationwide database study, 14 the incidence of ankle arthroscopy has outpaced the use of shoulder, knee, and elbow arthroscopy in recent years. However, upon review of recent ACGME case log studies, 16 , 29 , 30 it seems that orthopaedic resident case exposure to ankle arthroscopy is lower than many other areas of arthroscopic surgery. For example, from 2016 to 2020, the average number of shoulder arthroscopy cases performed increased from 69 to 79.7, representing a 15.5% increase.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Over this same time period, the average number of knee arthroscopy cases decreased by 2.6%. 30 However, knee arthroscopy appears to be the most commonly performed arthroscopic procedure among residents, as the average number of cases performed in 2020 was 111. Similar to ankle arthroscopy, resident case exposure to elbow arthroscopy and hip arthroscopy is relatively low and stagnant.…”
Section: Discussionmentioning
confidence: 99%